PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN EDUCAPLAY TERHADAP HASIL BELAJAR PENDIDIKAN PENCASILA SISWA KELAS V UPT SPF SD GALANGAN KAPAL 1 KECAMATAN TALLO - Fadilah, Nurul; Andi Nurfaizah AP; Amrah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the use of Educaplay learning media in Pancasila education learning, to determine the difference before and after using Educaplay learning media, and to identify the effect of using Educaplay learning media on students’ learning outcomes in Pancasila education for fifth grade students at UPT SPF SD Galangan Kapal 1. This research is classified as an experimental study with a quantitative approach. The research design employed in this study is a Quasi-Experimental Design with the Nonequivalent Control Group Design type. The population of this study consisted of all students at UPT SPF SD Galangan Kapal 1. The sample included 18 students from class V A and 16 students from class V B, selected using a purposive sampling technique. Data were collected through observation sheets on the implementation of learning media and learning outcome tests. Data were analyzed using descriptive and inferential statistics. The results of the descriptive analysis showed that the percentage of learning implementation using Educaplay learning media was categorized as good in the first meeting and very good in the second meeting. The inferential analysis showed a significance value of p = 0.001, which is smaller than α = 0.05, based on the independent sample t-test. This indicates a significant difference in post-test results between the experimental and control groups. These findings demonstrate that the improvement in students’ learning outcomes in the experimental group was higher than in the control group. This is supported by the higher average post-test scores of students in the experimental group compared to those in the control group. Therefore, it can be concluded that: (1) the learning process using Educaplay learning media is in the very good category, (2) test results indicate an improvement in students’ learning outcomes, and (3) there is a significant effect of using Educaplay learning media on students’ learning outcomes in Pancasila education for fifth grade students at UPT SPF SD Galangan Kapal 1.